Recovery and Half-Life of von Willebrand Factor-Cleaving Protease after Plasma Therapy in Patients with Thrombotic Thrombocytopenic Purpura - Furlan, Miha; Robles, Rodolfo; Morselli, Beat; Sandoz, Pierre; Lämmle, Bernhard (Thrombosis and Haemostasis, 1999)
Plasma exchange using fresh-frozen plasma (FFP) for replacement was given to two brothers during a relapse of thrombotic thrombocytopenic purpura (TTP). A constitutional deficiency of von Willebrand factor(vWF)-cleaving protease had been previously established in both patients. No inhibitor of vWF-cleaving protease was present in patients’ plasmas. They received plasma exchange for four and three consecutive days, respectively. In both patients, the activity of vWF-cleaving protease after the first plasmapheresis session was evaluated and was found to be virtually identical to anticipated activity calculated from predicted patient plasma volume and volume of exchanged plasma. Pathologic platelet counts and lactate dehydrogenase levels were normalized in both patients within 4-6 days. The biologic half-life of vWF-cleaving protease was determined in these patients following the last plasma exchange. The respective half-lives of 3.3 and 2.1 days represent the lowest known clearance rates of proteases in circulating human plasma.Another patient with relapsing TTP was treated with plasma exchange and/or plasma infusion for 10 consecutive days during the first relapse, 221-231 days after the initial TTP event. Pharmacokinetic studies of vWF-cleaving protease were performed after plasma exchange on day 221 and after plasma infusion on day 231. High level of an IgG in patient plasma, capable of completely inhibiting protease activity in an equal volume of normal plasma, had been established prior to first plasmapheresis. There was no measurable protease activity at any time during plasma therapy. Following plasma exchange, the level of the inhibitor was transiently slightly depressed. After 10 days of plasma therapy, the concentration of the inhibitor in patient plasma was increased about 5-fold. We suggest that, in contrast to protease deficient patients without circulating inhibitor, complementary therapy including immunosuppressive treatment, vincristine and/or splenectomy is indicated in patients with acquired inhibitors of vWF-cleaving protease. Testing for vWF-cleaving protease inhibitor may be useful in predicting the response to plasma exchange in patients with TTP.